2022
DOI: 10.1039/d1qi01629f
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing hydrogen production by AB hydrolysis with Pt@cobalt oxide/N,O-rich carbon and alkaline ultrasonic irradiation

Abstract: Non-precious metal oxide/carbon hybrid has been identified as a promising platform to stabilized precious metals for ammonia borane (AB) hydrolysis to produce hydrogen, whereas their facile and environmental-friendly synthesis remains...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 73 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…10(b) and (c)). 49–51 In Fig. 10(d) and (e), by comparing the conversion rate of unsaturated organic matter for 5 cycles with the two demulsification methods, it can be seen that the addition of NaOH has little effect on the conversion rate of unsaturated organic matter, and the selectivity for hydrogenation products was basically the same (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…10(b) and (c)). 49–51 In Fig. 10(d) and (e), by comparing the conversion rate of unsaturated organic matter for 5 cycles with the two demulsification methods, it can be seen that the addition of NaOH has little effect on the conversion rate of unsaturated organic matter, and the selectivity for hydrogenation products was basically the same (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Iron-, cobalt-and nickel-based oxides containing supports have also attracted much attention owing to their inherently high electrocatalytic performance. For example, de Oliveira et al [137] found that composites of nano nickel oxides (NiO x ) with commercial Pt/C catalyst (Fig. 8(c)) facilitate oxidation of adsorbed H atoms by the OH species at Ni sites on the Pt surface, which leads to high electrocatalytic performance.…”
Section: Carbon/oxidesmentioning
confidence: 99%
“…[136], copyright 2022, American Chemical Society, Ref. [137], copyright 2017, Elsevier, and Ref. [139], copyright 2017, American Chemical Society.…”
Section: (B)) [143]mentioning
confidence: 99%
“…Hence, it is necessary to develop cheap and efficient non‐noble metal catalysts. [ 14 ] To improve catalytic activity (CA), selectivity and conversion rate under environmental conditions are crucial to developing safe and efficient hydrogen storage. [ 15–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to develop cheap and efficient non-noble metal catalysts. [14] To improve catalytic activity (CA), selectivity and conversion rate under environmental conditions are crucial to developing safe and efficient hydrogen storage. [15][16][17] In this regard, cobalt-boride (Co-B) provided an inexpensive and effective catalyst for the hydrolysis of AB, [18,19] and a wide variety of Co-B was reported for improving the hydrolysis performance, such as unsupported Co-B, [20] supported Co-B, [21] and multialloyed Co-B.…”
Section: Introductionmentioning
confidence: 99%